The Relationship Between Phonemic Awareness, Vocabulary and Musical Abilities in 5-6-year old Children in Kindergartens - Šebianová, Kristína (Open Access Indonesia Journal of Social Sciences, 2024)
Young children (5-6 years old) are building strong foundations in language and music. Their phonemic awareness is developing, allowing them to identify and manipulate sounds in words. Vocabulary is rapidly expanding, with children learning new words and their meanings. Musical abilities are blossoming, with many children enjoying singing, keeping rhythm, and exploring instruments. However, there can be variations in these skills, and even gender differences in performance on some tasks. This study investigated the phonemic awareness, vocabulary, and musical abilities of 5-6-year-old children. We explored potential correlations between these domains and any gender differences in performance. Forty children (20 girls and 20 boys) from three kindergartens (two urban, one rural) were tested in June 2022. Three assessments were employed: Eľkonin's test of phonemic awareness, COWAT speech fluency test (vocabulary), and Bentley's test of musical abilities. Pearson's correlation coefficient analyzed relationships between the tests. A positive correlation was found between all three tests, suggesting potential links between phonemic awareness, vocabulary, and musical abilities. Interestingly, girls outperformed boys significantly in both Eľkonin's and Bentley's tests. Within Eľkonin's test, children achieved the highest scores in syllable synthesis (subtest No. 4) and the lowest scores in syllable deletion (subtest No. 10). This study suggests a connection between phonemic awareness, vocabulary, and musical abilities in young children. Additionally, it highlights potential gender differences in specific aspects of these domains. Further research is needed to explore the cause of these findings and their implications for early childhood education.